2010
DOI: 10.1097/jto.0b013e3181c3f4f1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study into the Incidence of Lambert Eaton Myasthenic Syndrome in Small Cell Lung Cancer

Abstract: Routine measurement of VGCC antibodies in patients without clinical LEMS is unlikely to assist either in management of SCLC or in assessment of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 21 publications
1
37
0
1
Order By: Relevance
“…Autoimmunity causing increased antibodies against the VGCC P/Q type in SCLC is the cause for LEMS [76,77]. In a prospective study to assess the incidence of clinical and subclinical LEMS in SCLC, 3% of patients had clinical LEMS and 5% were seropositive without clinical manifestation [78 ]. The prevalence of LEMS in SCLC has been estimated at to be 1-1.6% [79,80].…”
Section: Autoimmune Channelopathiesmentioning
confidence: 99%
“…Autoimmunity causing increased antibodies against the VGCC P/Q type in SCLC is the cause for LEMS [76,77]. In a prospective study to assess the incidence of clinical and subclinical LEMS in SCLC, 3% of patients had clinical LEMS and 5% were seropositive without clinical manifestation [78 ]. The prevalence of LEMS in SCLC has been estimated at to be 1-1.6% [79,80].…”
Section: Autoimmune Channelopathiesmentioning
confidence: 99%
“…4 Three previous studies were designed to establish the prevalence of PNDs in SCLC; one found 2% PND prevalence (3/150) among patients with SCLC from 5 UK centers, 5 but no antibodies were measured. The other 2 studies looked exclusively for Lambert-Eaton myasthenic syndrome (LEMS), finding the prevalence of LEMS in SCLC to be 3% (4/148 6 and 2/63, 7 respectively). Thus the frequency of the entire range of PNDs and neuronal antibodies in SCLC has not been determined systematically.…”
mentioning
confidence: 99%
“…Oft kommt es zu autonomen Störungen. Etwa 3 % aller Patienten mit einem SCLC haben klinisch und elektrophysiologisch ein LEMS [ 68 ] und 60 % der Patienten mit einem LEMS haben einen assoziierten Tumor, meist ein SCLC oder Lymphom.…”
Section: Seltenere Paraneoplastische Syndrome Des Zentralen Nervensysunclassified